2016
DOI: 10.3847/0004-637x/829/2/83
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Charge Exchange Contribution to the Rosat All Sky Survey Maps

Abstract: DXL (Diffuse X-ray emission from the Local Galaxy) is a sounding rocket mission designed to estimate the contribution of Solar Wind Charge eXchange (SWCX) to the Diffuse X-ray Background (DXB) and to help determine the properties of the Local Hot Bubble (LHB). The detectors are large-area thin-window proportional counters with a spectral response similar to that of the PSPC used in the ROSAT All Sky Survey (RASS). A direct comparison of DXL and RASS data for the same part of the sky viewed from quite different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…One of the objectives of the present study has been to observe the ROSAT-discovered EXS under a condition wherein the variable and anisotropic SWCX contribution ( §3.2.1) is considered to be much lower than in the ROSAT R5 band (0.56-1.21 keV), where the SWCX contribution is estimated (Uprety et al 2016) to be 6% ± 4% (statistical) ±4% (systematic). The present SSC results are expected to satisfy this requirement, for the following reasons.…”
Section: Possible Contribution By the Swcx Componentmentioning
confidence: 99%
“…One of the objectives of the present study has been to observe the ROSAT-discovered EXS under a condition wherein the variable and anisotropic SWCX contribution ( §3.2.1) is considered to be much lower than in the ROSAT R5 band (0.56-1.21 keV), where the SWCX contribution is estimated (Uprety et al 2016) to be 6% ± 4% (statistical) ±4% (systematic). The present SSC results are expected to satisfy this requirement, for the following reasons.…”
Section: Possible Contribution By the Swcx Componentmentioning
confidence: 99%
“…10). Nevertheless, recent results from the December 2012 Diffuse X-rays from the Local galaxy (DXL) rocket flight have conclusively demonstrated that ∼ 40% of background emissions in a direction of very low cosmic background intensity originate from the He focusing cone and not the local hot bubble surrounding the heliosphere Uprety et al 2016;Liu et al 2017). Koutroumpa et al (2007) employed a dynamic model to simulate the effects of a propagating corotating interaction region on line of sight soft X-ray emissions.…”
Section: Modeling Soft X-ray Emissions From the Heliospherementioning
confidence: 99%
“…The Diffuse X-ray emission from the Local galaxy (DXL) sounding rocket flight was designed to isolate the spatial variation of soft X-ray emissions from the He focusing cone (Galeazzi et al 2011Uprety et al 2016). The look direction of the local midnight launch on 2012 December 13 from the White Sands Missile Range in New Mexico avoided soft X-rays from charge exchange in the vicinity of the Earth's magnetosphere and pointed antisunward through the maximum emission region of the heliospheric He focusing cone, a direction towards the galactic anti-center which avoids bright galactic soft X-ray sources.…”
Section: The Heliospherementioning
confidence: 99%
“…As mentioned in Section 5.2, at high latitudes we are unable to separate the local plasma from the low temperature component of the halo, which affects our derived values for emission measure, as well as possibly temperature. Liu et al (2017) combined SWCX maps from Uprety et al (2016) with data from Snowden et al (1998) to estimate the local and distant astrophysical contributions to the R12 band. In Table 9, we compare the results of our spectral model fits to that work.…”
Section: The Local Hot Bubblementioning
confidence: 99%
“…Combined contribution of fast and slow SWCX model components inTables 3 and 4to the ROSAT energy bands R1 and R2, compared to estimates for the RASS R1 and R2 maps given byUprety et al (2016). All uncertainties are reported at 90% confidence level.…”
mentioning
confidence: 99%